Compostagem em áreas urbanas: lições aprendidas no projeto feiras e jardins sustentáveis da Lapa, São Paulo- SP, Brasil - Galvão, Rafael Golin (2019)
Solid waste is one of the most important by-products of the urban way of life, consuming the public budget and generating social, health and environmental impacts. In this scenario, countries have been promoting changes, with stricter laws and sustainability practices. Composting is effective in the treatment of organic waste and the product obtained in the process can be used in gardening and agriculture. In Brazil, Federal Law No. 12.305 (2010), which instituted the National Solid Waste Policy, establishes that cities must create local plans to address the problems of inadequate management of solid urban waste. The objective of the research was to identify and extract lessons learned in the Sustainable Street Markets and Gardens Project, which from the proper disposal of organic waste from street markets and tree pruning in the city of São Paulo with a view to its application in other composting yards. To prepare the research instrument, references to the treatment of organic waste were identified in the literature and the composting process carried out in Lapa was systematized through documentary records and the performance of the participating researcher. With the information recorded, eight preliminary statements and respective justifications were prepared, sent by e-mail to eleven professionals involved in the project. Nine returned contact and were interviewed, where the eight lessons learned were fully or partially validated. The interviews were transcribed and the main experiences acquired were captured in order to later rewrite the lessons learned, inserting facts and evidence presented by the participants. The eight lessons learned constitute an important tool for the implementation of new projects, since they add practical experiences to the theoretical foundation and address issues considered paradigms in the management of organic waste, such as the decentralization of the process and implementation in urbanized areas. The planning and critical analysis of the implemented methodology, the integration between the public authorities and the private sector and the analysis of environmental legislation also culminated in lessons learned from the experience during the pilot project. Themes with consistent theoretical basis: odor generation, segregation at the origin and temperature control, were addressed, bringing to the discussion the practical experience of the project in the city of São Paulo that show that it is possible to give adequate destination to organic waste in urban centers, near the generating source, provided that the premises listed in this work are respected. It is expected that the lessons learned will be a reference in the expansion of the program in the municipality and to other cities, promoting the recycling of organic waste.